Semi-active control of sliding isolated bridges using MR dampers an experimental and numerical study. - Sahasrabudhe, Sanjay S. (Earthquake engineering & structural dynamics.)
Sliding base isolation systems used in bridges reduce pier drifts, but at the expense of increased bearing displacements under near source pulse type earthquakes. It is common practice to incorporate supplemental passive non-linear dampers into the isolation system to counter increased bearing displacements. Non-linear passive dampers can certaintly reduce bearing displacements, but only with increased isolation level forces and pier drifts. The semi-active controllable non-linear dampers, which can vary damping in real time, can reduce bearing displacements without further increase in forces and pier drifts; and hence deserve investigation. In this study performance of such a 'smart' sliding isolation system, used in a 1:20 scaled bridge model, employing semi-active controllable magneto-rheological (MR) dampers is investigated, analytically and experimentally, under several near fault earthquakes. A non-linear analytical model, which incorporates the non-linearities of sliding bearings and the MR damper, is developed. A Lyapunov control algorithm for control of the MR damper is developed and implemented in shake table tests. Analytical and shake table test results are compared. It is shown that the smart MR damper reduces bearing displacements further than the passive low and high damping cases, while maintaining isolation level forces less than the passive high damping case.